2014
DOI: 10.1186/1742-6405-11-21
|View full text |Cite
|
Sign up to set email alerts
|

HCV RNA viral load is independent from CD4 cell count and plasma HIV RNA viral load in immunocompetent HIV-HCV co-infected patients: a 3-years follow-up study

Abstract: BackgroundHCV RNA viral load is an important predictor of sustained virological response and, recently, a significant correlation with liver fibrosis was described. We investigated on possible influence of clinical and viro-immunological variables on HCV viral load in HIV-HCV co-infected patients over a study time of three years (2009-2012).MethodsWe retrospectively enrolled 98 adult patients with a diagnosis of chronic HIV infection in 2009, a diagnosis of chronic HCV infection with a detectable plasma HCV RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The HBV immunity rate was lower than that observed among HIV/HCV-infected individuals from China [ 31 ]. Most of the HCV+ individuals had a high viral load compared with a previous study conducted among HIV/HCV-infected individuals [ 32 ]. HCV genotype 1 was the most prevalent, similar to that observed among HIV/HCV-coinfected and HCV-monoinfected individuals in Brazil [ 12 , 33 ].…”
Section: Discussionmentioning
confidence: 87%
“…The HBV immunity rate was lower than that observed among HIV/HCV-infected individuals from China [ 31 ]. Most of the HCV+ individuals had a high viral load compared with a previous study conducted among HIV/HCV-infected individuals [ 32 ]. HCV genotype 1 was the most prevalent, similar to that observed among HIV/HCV-coinfected and HCV-monoinfected individuals in Brazil [ 12 , 33 ].…”
Section: Discussionmentioning
confidence: 87%
“…The subjects were defined with undetectable plasma HIV viremia when no HIV RNA determination higher than 50 copies/ml was obtained during the entire study period; the detection of one viral blip (defined as a single plasma HIV RNA value between 50 and 500 copies/ml followed by a viral load not detectable) a year was acceptable [11]. The definition of detectable HIV viremia included any other result [12].…”
Section: Methodsmentioning
confidence: 99%
“…Many studies from India and around the world have reported that HBV/HCV coinfection did not affect CD4+ T-cell counts and HIV-1 viral load suppression after ART. [ 5 6 7 9 ] It has been hypothesized that splenic sequestration of lymphocytes due to HBV-related hepatic fibrosis may be responsible for lower CD4+ T-cell recovery. [ 30 ] Many underlying comorbid conditions, other OIs, small sample size, and lack of compliance/adherence may affect these results.…”
Section: Discussionmentioning
confidence: 99%
“…Although various authors have evaluated the short-term response to ART on HIV/HBV and HIV/HCV coinfected individuals, the impact of HBV and HCV on HIV treatment outcomes is not clear due to variable reports. [ 5 6 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%